ANALISIS KINERJA ANGGARAN BELANJA PADA BADAN PUSAT STATISTIK (BPS) KABUPATEN TANA TORAJA - Dwibin Kannapadang (Paulus Journal of Accounting (PJA), 2021)
This study aims to analyze the budget performance of the Central Statistics Agency for Tana Toraja Regency in 2018-2020. The method used is a quantitative descriptive method which is processed using a shopping performance analysis tool. The results showed that (1) the analysis of the expenditure variance on the expenditure realization of the Central Statistics Agency of Tana Toraja Regency showed good budget performance where the realization of wxpenditure did not ecceed the previously targeted budget; (2) spending growth analysis shows spending growth, from 2018-2020 there was an average positive growth of 6.39%; (3) the compability analysis of expenditures shows that the harmonization of expenditures is not balanced where BPS of Tana Toraja Regency only focuses on operating expenditures rther than capital expenditures; (4) BPS Tana Toraja Regency has made expenditure sufficiency by using a budget that does not exceed its realization. However, there were two programs in 2018 that did not run efficiently. However, the overall performance of the Tana Toraja Regency BPS budget for 2018-2020 can be said to be good.